A fast regulation algorithm for low voltage in regional grids with high uncertainty and high penetration of wind and solar loads at the grid end - Heran Kang; Hongyang Liu; Lijun Zhao; Jie Sun; Yong Shi; Wei Yue; Miaoyong Feng (PLoS ONE, 2025)
To address the issue of low voltage fluctuations at the grid end caused by the high penetration of wind and solar loads in the power grid, a fast low-voltage regulation algorithm is proposed. This algorithm aims to resolve the stability challenges brought by the uncertainty of wind and solar power sources. The method involves predicting the power output fluctuations of wind turbines, photovoltaics, and loads. A multi-objective fast regulation model is constructed, incorporating safety, efficiency, and cost factors, with corresponding constraints established. A simultaneous optimization transmission mechanism is adopted to achieve rapid voltage regulation. Results indicate that the algorithm has a high degree of prediction accuracy, rapidly restoring voltage to normal levels and maintaining stability within a tolerance level of 0.95 or higher. In conclusion, this algorithm effectively improves the stability and reliability of the power grid, providing a practical technical solution for handling high penetration levels of wind and solar energy in the grid.